Preferential protection of domains ii and iii of bacillus thuringiensis cry1aa toxin by brush border membrane vesicles (2010)
Título español: Protección preferencial de los dominios II y III de la toxina Cry1Aa de Bacillus thuringiensis en Vesículas de Membrana de Borde de Cepillo Abstract The surface exposed Leucine 371 on loop 2 of domain II, in Cry1Aa toxin, was mutated to Lysine to generate the trypsin-sensitive mutant, L371K. Upon trypsin digestion L371K is cleaved into approximately 37 and 26 kDa fragments. These are separable on SDS-PAGE, but remain as a single molecule of 65 kDa upon purification by liquid chromatography. The larger fragment is domain I and a portion of domain II (amino acid residues 1 to 371). The smaller 26-kDa polypeptide is the remainder of domain II and domain III (amino acids 372 to 609). When the mutant toxin was treated with high dose of M. sexta gut juice both fragments were degraded. However, when incubated with M. sexta BBMV, the 26 kDa fragment (domains II and III) was preferentially protected from gut juice proteases. As previously reported, wild type Cry1Aa toxin was also protected against degradation by gut juice proteases when incubated with M. sexta BBMV. On the contrary, when mouse BBMV was added to the reaction mixture neither Cry1Aa nor L371K toxins showed resistance to M. sexta gut juice proteases and were degraded. Since the whole Cry1Aa toxin and most of the domain II and domain III of L371K are protected from proteases in the presence of BBMV of the target insect, we suggest that the insertion of the toxin into the membrane is complex and involves all three domains. Key words: Bacillus thuringiensis, site directed mutagenesis,  -endotoxin. Resumen La superficie de la toxina Cry1Aa, en el asa 2 del dominio II contiene expuesta la leucina 371, la cual fue modificada a lisina produciendo una mutante sensible a la tripsina, L371K. Esta mutante produce dos fragmentos de 37 y 26 kDa por acción de la tripsina que son separables por SDS-PAGE, pero que a la purificación por cromatografía líquida se mantienen como una sola molécula de 65 kDa. El fragmento grande contiene al dominio I y una parte del dominio II (aminoácidos 1 al 371). El polipéptido de 26 kDa contiene la parte restante del dominio II y dominio III (aminoácidos 372 al 609). Cuando la toxina mutante fue tratada con dosis altas de jugo intestinal de Manduca sexta, ambos fragmentos fueron degradados. Sin embargo, cuando fueron incubados en VMBC de M. sexta, el fragmento de 26 kDa fue protegido preferencialmente de las proteasas intestinales. Como se ha reportado, la toxina silvestre Cry1Aa también es protegida de la degradación de las proteasas cuando es incubada en VMBC de M. sexta. Sin embargo, cuando se adicionó VMBC de ratón a la mezcla de reacción, ni la toxina Cry1Aa ni la mutante L371K mostraron resistencia a las proteasas y fueron degradadas. Dado que la toxina completa de Cry1Aa y casi todo de los dominios II y III de L371K están protegidos de proteasas en presencia de VMBC del insecto, este estudio sugiere que la inserción de la toxina en la membrana involucra los tres dominios. Palabras clave: Bacillus thuringiensis, mutagénesis sitio dirigida, - endotoxina